Preparation of a geographical database of the morphometric characteristics of the watersheds in northern Sinjar using geographic information systems (GIS) - Raed Mahmood Faisal (College of Education for Pure Sciences, 2013)
ABSTRACT This research aime to build geographyic data base with morphometric variables for 26 watersheds in northern sinjar by using data resoncces such as (SRTM) Digital elevation models programs that were used (Arc Gis 9.3 - Arc hydro 1.3 -Spatial Analyst-). Data base was used to extract measurement of 25 morphometric object that has shape characteristics or drainage or topography. Analysis results showed that most of the watersheds were almost rectangular (0.42) with a triangular formation) 0.15). First and second order in drainage were the most and longest (1421.37- 303.16) KM, (1812 -417) valley. Watersheds gave small value in longitudinal and numerical drainage density, and it was (1.81) KM (1.55) vallies, with rough texture severe topography (20.35(.